The impact of Bank of Japan’s exchange-traded fund purchases - Hattori, Takahiro; Yoshida, Jiro (Journal of Financial Stability, 2023)
The Bank of Japan (BOJ) enhanced its large-scale asset purchases in October 2010 by purchasing equity exchange-traded funds (ETFs). This study is the first to demonstrate that the BOJ provides downside protection for stock prices through the countercyclical purchase of ETFs. The BOJ responds to a large negative stock return during the overnight and morning periods, and submits purchase orders during lunchtime. Using the BOJ’s March 2020 announcement of doubling the annual purchase amount during the COVID-19 pandemic, this study also finds that the announcement effect is small and temporary. In contrast, the flow effect of the actual purchases is significant and increases. The BOJ’s countercyclical ETF purchase prevents equity risk premia from rising during an economic downturn.